The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1983-1447.2021.20200274
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the serious game for learning in nursing: systematic review

Abstract: Objective To identify the effectiveness of the serious game in improving learning outcomes compared to the different teaching strategies used in the education of nursing students. Method Systematic review, conducted from July 2019 to May 2020, at PubMed®, Scopus, CINAHL, Web of Science and LILACS. Studies of experimental and quasi-experimental design were included, with no delimitation of time frame, aimed at nursing students, who approached the use of the serious game as the main teaching strategy compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(90 reference statements)
0
3
0
1
Order By: Relevance
“…This study has some limitations, such as the single-center design. The importance of developing multicenter research that addresses the adoption of the SGs as a learning strategy for best practice is given by obtaining larger samples for more generalizable results and by sharing resources between collaborative sites and promoting networks 27 . Also, our study did not have a control group, therefore the findings cannot be compared to another training method and the results may pose risks in terms of reliability.…”
Section: Discussionmentioning
confidence: 99%
“…This study has some limitations, such as the single-center design. The importance of developing multicenter research that addresses the adoption of the SGs as a learning strategy for best practice is given by obtaining larger samples for more generalizable results and by sharing resources between collaborative sites and promoting networks 27 . Also, our study did not have a control group, therefore the findings cannot be compared to another training method and the results may pose risks in terms of reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The several advantages of SGs for instructional purposes, such as enhancing the engagement and motivation of the players, achieving optimal attention, improving learners' skills in an enjoyable way, providing an interactive environment, giving quick feedback and progress records, and affording teamwork among learners, led to their popularity in the educational fields [ [6] , [7] , [8] ]. Accordingly, many studies have been conducted to show the positive effect of SGs on education and learning [ [9] , [10] , [11] ]. For instance, Tubelo et al revealed that the SGs were an effective tool for improving the students’ knowledge of primary healthcare content [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Tubelo et al revealed that the SGs were an effective tool for improving the students’ knowledge of primary healthcare content [ 10 ]. Nascimento et al concluded in their systematic review that SGs can be used as an effective technology for nursing learning compared to other teaching methods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inicialmente, estos juegos fueron desarrollados para formar profesionales en el ámbito laboral, pero a medida que se comprobó su eficacia, su uso se fue ampliando al ámbito de la educación escolar y universitaria. Su relevancia quedó demostrada por una revisión sistemática (6) realizada en 2021, que mostró una mejora en el aprendizaje y la satisfacción de los estudiantes luego del uso del serious game, según la evaluación de estudios experimentales publicados.…”
Section: Introductionunclassified